2013
DOI: 10.1080/19475411.2011.652218
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitor and nanoscale research towards electrochemical energy storage

Abstract: Electrochemical capacitors, also known as supercapacitors or ultracapacitors, have received much attention from research and development to industrialization, owing to their promise to deliver high levels of electrical power and offer long operating lifetimes. They are considered ideal candidates for energy storage in high-power applications. Benefiting from intensive nanoscale research in recent decades, remarkable improvements and development of supercapacitive energy storage systems have been achieved. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 80 publications
1
38
0
Order By: Relevance
“…Another class of active electrode materials for supercapacitors is transition metal oxides like NiO, Co 3 O 4 , ZnO, MnO 2 etc. [17][18][19] . Studies have revealed that binary mixed oxides of transition metal * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of active electrode materials for supercapacitors is transition metal oxides like NiO, Co 3 O 4 , ZnO, MnO 2 etc. [17][18][19] . Studies have revealed that binary mixed oxides of transition metal * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…where 'E' is the energy density in Wh/Kg, 'C' is the specific capacitance in F/g and 'V' is the potential P ¼ E t (7) where 'P' is the power density in W/Kg and't' is the discharge time in seconds A plot of energy and the corresponding power density at different current densities such as 0.2, 0.5, 1, 2.5 and 5 A g À1 are given in Fig. 12 [42].…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…The carbon materials have been investigated for their supercapacitance properties owing to their mesoporous/ microporous structure which allows easy diffusion of ions and adaptability of these materials for volumetric changes during charge and discharge cycles thus improving the cyclability [7,8]. Even though the surface area of these carbon materials is high, all of it is not accessible to electrolytic solution consequently lowering specific capacitance and energy density [9].…”
Section: Introductionmentioning
confidence: 99%
“…Smart materials are attracting increasing interest especially in the era of the fourth industrial revolution (Industry 4.0) and circular economy. Smart polymer nanocomposites (SPN) which can be derived from shape memory polymer [3][4][5][6], stimuli-active polymers [7], smart electrorheological (ER) and magnetorheological (MR) polymer [8][9][10][11], self-healing polymer [12,13], self-cleaning polymer [14][15][16][17], self-heating polymer [18], self-sensing polymer [19], energy-harvesting and energy storage polymer [20][21][22][23][24][25][26][27] are the latest hot research topics. The addition of nanofiller can increase the performance of the SPN (e.g., shape fixity, shape recovery, self-healing ability) due to their high specific surface area, nucleating effects, reinforcing effects, and inherent functionalities (e.g., thermal conductivity, electrical conductivity) [3].…”
Section: Introductionmentioning
confidence: 99%